Influence of Incubation Temperature on 9,10-Anthraquinone-2-Sulfonate (AQS)-Mediated Extracellular Electron Transfer - Liu, Wei; Wu, Yundang; Liu, Tongxu; Li, Fangbai; Dong, Hui; Jing, Meiqing (Frontiers in Microbiology, 2019)
The electron shuttling process has been recognized as an important microbial respiration process. Because the incubation temperature can influence both the reactivity of electron mediators and cell growth, it may also affect the electron-shuttle-mediated extracellular electron transfer (EET) process. Here, the effect of incubation temperature (22–38 °C) was investigated in a bioelectrochemical system (BES) using Shewanella oneidensis MR-1 and 50 μM of 9,10-anthraquinone-2-sulfonate (AQS). We found that current generation increased as the temperature was increased from 22 to 34 °C and then decreased sharply at 38 °C. The biofilm biomass, as indicated by the total protein extracted from the electrode, increased as the temperature increased from 22 to 34 °C and then decreased at 38 °C, mirroring the current generation results. These results were further confirmed by increasing the temperature slowly, step-by-step, in a single BES with a constant biofilm biomass, suggesting that the EET rates could be substantially influenced by temperature, even with the same biofilm. The effects of temperature on the AQS bioreduction rate, c-type cytochrome (c-Cyts)-bound-cofactor-mediated EET, the AQS mid-point potential, and the AQS diffusion coefficient were studied. From these results, we were able to conclude that temperature influenced the EET rates by changing the c-Cyts-bound-cofactor-mediated EET process and the AQS bioreduction rate, and that the change in biofilm formation was a dominant factor influencing the overall EET rates. These findings should contribute to the fundamental understanding of EET processes. Moreover, optimization of the operating parameters for current generation will be helpful for the practical application of bioelectrochemical techniques.